MANAGEMENT SYSTEMS: SOIL COVER AND COMPACTION, LONGITUDINAL DISTRIBUTION, AND YIELD OF SOYBEAN CROP - Cortez, Jorge W.; Pusch, Maiara; Silva, Rouverson P. da [UNESP]; Rufino, Mauricio; Anghinoni, Matheus (Soc Brasil Engenharia Agricola, 2019)
The way the soil is managed can influence its structuring and, consequently, crop yield. Thus, this study aimed to evaluate the effect caused by the management systems plowing followed by two intermediate harrowing operations, intermediate harrowing, chiseling, chiseling followed by intermediate harrowing, cross chiseling followed by intermediate harrowing, and non-tillage on soil and agronomic attributes of the soybean crop. A randomized block design with four replications was used. The percentage of soil cover, soil resistance to penetration, number of plants per meter, longitudinal distribution of seedlings, and soybean yield were evaluated. The data were submitted to analysis of variance by the Tukey test at 5% probability, and use of geostatistics for soil resistance to penetration. The system without soil tillage provides the best straw preservation but affects the longitudinal distribution of soybean seedlings. The use of intermediate harrowing for managing crop residues or soil tillage leads to the greatest compaction problems. Chiseling is efficient in maintaining compaction values below critical values up to a depth of 0.20 m when working at 0.35 m. Soil yield is not affected by soil management systems when the pluviometric regime is adequate to crop requirements.
Keywords: resistance to penetration; geostatistics; soil tillage